Keterampilan Menulis Puisi Bebas Pada Mata Pelajaran Bahasa Indonesia Kelas IV MI - Farichah Nur' Ajmiy; Nanang Khoirul Umam (Elementary Teacher Education Program, Majalengka University, 2023)
In this era, learning the Indonesian language is very important for children. Learning Indonesian is very important because it will enable children to understand the correct grammar. The purpose of the research is to find out the skills that students have in writing free poetry. The method used in this research uses qualitative descriptive through the type of case study research. Data collection in this study uses observation techniques, tests, and interviews. As well, descriptive analysis techniques are used in this study. This study shows that there are still some students who like and dislike Indonesian language lessons. Students still have difficulty composing poetry and understanding the elements of poetry, according to the skills of free poetry writing. However, there are still students who enjoy doing it and feel easy to write poetry. Therefore, the role of the teacher in helping students learn Indonesian and develop the ability to write poems freely is important. As well as the role of the school that improves the quality of teachers so that they can be professional and make learning activities interesting